Mobile social media use and life satisfaction among adolescents: a moderated mediation model - Meng, Sujie; Kong, Fanchang; Dong, Wanghao; Zhang, Ying; Yu, Tingting; Jin, Xiangdong (Frontiers in Public Health, 2023)
Introduction Adolescence is a sensitive transitional period accompanied by great physical, mental, and behavioral changes. Therefore, maintaining physical and mental health is crucial to the growth and development of adolescents. As one of the important indicators of mental health, the influencing factors of life satisfaction have been widely concerned by scholars. In recent years, with the rapid development of Internet technology, mobile social media has penetrated into all aspects of adolescents’ life, which has a subtle impact on their physical and mental health. Existing studies have indicated that mobile social media use can affect adolescents’ life satisfaction. However, little is known about the mediating and moderating mechanisms linking this association. This study developed a moderated mediation model to examine the mediating role of meaning in life and the moderating role of childhood psychological maltreatment. Methods A total of 1,198 adolescents across four provinces and municipalities of China completed questionnaires on mobile social media use, life satisfaction, meaning in life, and childhood psychological maltreatment. Results After controlling for gender and age, the results demonstrated that mobile social media use was positively associated with life satisfaction and meaning in life among adolescents. Moreover, meaning in life fully mediated the association between mobile social media use and life satisfaction. Finally, the association between mobile social media use and life satisfaction, as well as that between mobile social media use and meaning in life, was moderated by childhood psychological maltreatment. Specifically, these associations are stronger for adolescents with high levels of psychological maltreatment. Discussion These findings shed light on the important mechanism underlying mobile social media use’s effects on adolescents’ life satisfaction, which is helpful to formulate targeted measures for improving adolescents’ life satisfaction.